TO A QUESTION OF THE PURPOSES, TASKS OF IMPLEMENTATION OF INTERNAL CONTROL IN THE CREDIT ORGANIZATIONS AND IN THE BANK OF RUSSIA - Yulia I. Panova (Модернизация, инновация, развитие, 2015)
Аrticle is devoted to comprehensive consideration and the characteristic of the purposes and tasks of the multi-level internal control exercised in Bank of Russia, to a procedure and creations of internal control, in article the interrelation of the purposes and components of internal control is traced, the control environment as one of the main a component of internal control is analyzed, powers of subjects of internal control are in detail stated. The attention is paid to control consideration as management functions, the developed list of the principles of creation of internal control and its types – preliminary, current and subsequent is provided.